Ulasan Buku ”Il Principe”(Sang Pangeran) Karya Niccolo Machiavelli - Muhammad Boim; Tri Rizky Wulandari; Beany Vas Quin; Amon Qulsepfriti; Adetiya Anggreni; Juwati Juwati; Julika Purwasih; Widiawati Widiawati; Nurliani Nurliani; Wiyah Wiyah; Sasa Sasa; Esyi Esyi (Institut Nalanda, 2023)
This review examines the classic book